Plans, sections and elevations : key buildings of the twentieth century. - Weston, Richard, 1953- (London : Laurence King, 2004)
Le Corbusier, Louis Kahn, Alvar Aalto, Aldo van Eyck, Frank Lloyd Wright, Peter Eisenman, Barcelona Pavilion, Villa Savoye, Palais Stoclet, Frank Gehry, Unity Temple, Lever House, Amsterdam Municipal, Renzo Piano, Rem Koolhaas, Villa Mairea, Maison de Verre, Farnsworth House, Einstein Tower, Tadao Ando For the first time, a student can now find all the key plans in one place. Featuring more than 100 of the most significant and influential buildings of the 20th century, this book includes both classic works by such seminal architects as Le Corbusier, Frank Lloyd Wright, Mies van der Rohe and Alvar Aalto, as well as those by more recent masters, such as Norman Foster, Frank Gehry and Rem Koolhaas. For each of the buildings included there are numerous, accurate scale plans showing each floor, together with elevations, sections and site plans where appropriate. All of these have been specially commissioned for the book and are based on the most up-to-date information and sources. There is also a concise text explaining the significant architectural features of the building and the influences it shows or generated, together with full-colour images. Cross-references to other buildings in the book highlight the various connections between these key structures.
Keywords: Bouwkunst